The Urgency of Philosophy of Science in the Context of Human Civilization: An Epistemological Analysis - Jannah, Miftahul; Warul Walidin (JIA (Jurnal Ilmu Agama), 2024)
This research aims to find out how the urgency of philosophy of science in the context of human civilization with epistemological analysis. An important part in creating and advancing human civilization is played by the philosophy of science. A thorough understanding of epistemology, the field of philosophy that deals with theory, offers a critical perspective on how people learn and develop science. With a focus on the epistemological viewpoint that serves as the foundation of scientific thinking, this article examines the importance of philosophy of science in relation to the advancement of human civilization. To gain a comprehensive understanding, this research uses descriptive qualitative research with a literature review. This study shows how the philosophy of science can guide human civilization towards more sustainable, knowledge-based and equitable growth. Philosophy of science plays a very important role in shaping human understanding of knowledge and the development of scientific methodology. Through critical analysis of basic concepts and epistemological approaches, philosophy of science helps us evaluate the validity of knowledge and the methods used in research. With the growing complexity of challenges facing humanity, such as climate change and social injustice, the critical thinking taught by philosophy of science is becoming increasingly relevant. In addition, philosophy of science contributes to innovation by encouraging reflective and interdisciplinary approaches in research. Therefore, the urgency of philosophy of science in the context of human civilization lies in its ability to facilitate ethical dialogue, encourage sustainable innovation, and ensure that the knowledge produced is relevant and beneficial to the whole of society.